THE ANALYSIS OF PSYCHOLOGICAL CONFLICTS THAT ARE EXPERIENCEDBY BLANCHE DUBOIS TO KNOW HER EMOTIONAL REACTION IN TENNESSEE WILLIAMS’ A STREETCAR NAMED DESIRE - Riwa Rambu Hada Enda (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This research aims to know the psychological conflict of Blanche DuBois and her emotional reaction after facing the conflicts. The research is a qualitative and library research. The data gathered are especially taken from the main source which is the play itself. Besides that, to support the study the writer gets some data from books and internet and the objective theory of literature. The study finds out that Blanche DuBois’ emotional reaction after facing:(1) approach-approach conflict is mild because there are all positive goals, she likes and enjoy that psychological conflicts; (2) avoidance-avoidance conflict is self-aggression because she blames herself for this conflict situation and displace aggression because she displaces the frustration to Stella; (3) approach-avoidance conflict is leave the psychological space because she cannot handle her psychological conflict anymore; (4) double approach-avoidance conflict is leave the psychological space because she prefers to refuse all the conflicts, refuse to face reality in her life. Keywords: literature, psychological conflicts, emotional reaction.